SAT0342 Treatment of postmenopausal women with osteoporosis for six years with denosumab: Three-year results from the freedom extension. (23rd January 2014) - Chapurlat, R.; Papapoulos, S.; Brown, J.P.; Franchimont, N.; Brandi, M.L.; Czerwiński, E.; Krieg, M.-A.; Man, Z.; Mellström, D.; Radominski, S.C.; Reginster, J.-Y.; Resch, H.; et al.
Abstract : Background: Denosumab (DMAb) is approved for the treatment of postmenopausal women with osteoporosis at increased risk for fracture. A favorable risk/benefit profile was demonstrated in the pivotal, 3-year FREEDOM trial. 1 The open-label, active-treatment FREEDOM extension study is evaluating the long-term efficacy and safety of DMAb for up to 10 years. Objectives: Report results from the first 3 years of the extension, representing up to 6 years of DMAb treatment. Methods: In the extension, each woman is scheduled to receive 60 mg DMAb every 6 months and supplemental calcium and vitamin D daily. For women given placebo during FREEDOM, the data here reflect 3 years of DMAb exposure (cross-over group). For women given DMAb during FREEDOM, the data reflect 6 years of DMAb exposure (long-term group). Results: There were 5928 women eligible for the extension. Of these, 4550 (77%) enrolled (2207 cross-over; 2343 long-term). In the first 3 years of DMAb treatment during the extension, the cross-over group had significant gains in bone mineral density (BMD) at the lumbar spine (9.4%) and total hip (4.8%), comparable to those observed in the long-term DMAb group during the first 3 years of FREEDOM (lumbar spine, 10.1%; total hip, 5.7%). In the long-term group, further significant increases in BMD occurred for cumulative 6-year gains of 15.2% at the lumbar spine and 7.5% at the total hip. After the 1st (cross-over) or 7th (long-term) DMAb dose, sCTX was rapidly and similarly reduced with the characteristic attenuation at the end of the dosing period. In the cross-over group, yearly incidences of nonvertebral, new vertebral, clinical vertebral, and clinical fractures were lower than those in the FREEDOM placebo group. Fracture incidence remained low in the long-term group. Incidences of adverse events (AEs) and serious AEs did not increase over time with DMAb. Two subjects in each group had AEs adjudicated to ONJ. Both cases in the cross-over group healed without further complications; one subject continues to receive DMAb. One case in the long-term group healed, while the other continues to be followed. There were no atypical femur fractures. Conclusions: DMAb treatment for 3 years in the cross-over group reproduced FREEDOM observations. DMAb treatment for 6 years (long-term group) continued to significantly increase BMD, maintained reduced bone turnover, and remained well tolerated. Fracture incidence remained low. References: Cummings et al. N Engl J Med. 2009;361:756 Disclosure of Interest: R. Chapurlat Grant/Research support from: Pfizer, Amgen, Servier, Consultant for: Amgen, Servier, Novartis, Roche, Lilly, S. Papapoulos Consultant for: Amgen, Eli Lilly, GSK, Merck, Novartis, J. Brown Grant/Research support from: Abbott, Amgen, Bristol-Myers Squibb, Eli Lilly, Merck, Novartis, Pfizer, Roche, sanofi-aventis, Servier, Warner Chilcott, Consultant for: Amgen, Eli Lilly, Merck, Novartis, sanofi-aventis, Warner Chilcott, Speakers Bureau: Amgen, Eli Lilly, Novartis, N. Franchimont Shareholder of: Amgen, Employee of: Amgen, M. Brandi Consultant for: Amgen, Servier, MSD, Roche, Glaxo, Eli Lilly, Nycomed, NPS, Pfizer, E. Czerwiński Grant/Research support from: Amgen, AstraZeneca, Danone Research, Eli Lilly, Merck Serono, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Servier, M.-A. Krieg: None Declared, Z. Man Grant/Research support from: Merck, Amgen, Lilly, Consultant for: Novartis, Merck, Sanofi aventis, D. Mellström: None Declared, S. Radominski Grant/Research support from: BMS, Pfizer, Amgen, Roche, Novartis, Speakers Bureau: Aventis, Lilly, Novartis, J.-Y. Reginster Grant/Research support from: BMS, Merck Sharp & Dohme, Rottapharm, Teva, Lilly, Novartis, Roche, GSK, Amgen, Servier, Consultant for: Servier, Novartis, Negma, Lilly, Wyeth, Amgen, GSK, Roche, Merckle, Nycomed, NPS, Theramex, UCB, H. Resch Consultant for: MSD, Lilly, Amgen, Sankyo, Roche, Servier, J. Román Grant/Research support from: Roche, MSD, Consultant for: Actelion, Pfizer, C. Roux Grant/Research support from: Amgen, Novartis, Consultant for: Amgen, Novartis, MSD, N. Daizadeh Shareholder of: Amgen, Employee of: Amgen, M. Geller Shareholder of: Amgen, Employee of: Amgen, S. Smith Shareholder of: Amgen, Employee of: Amgen, R. Wagman Shareholder of: Amgen, Employee of: Amgen, S. Cummings Consultant for: Amgen, H. Bone Grant/Research support from: Merck, Amgen, Nordic Bioscience, Novartis, Takeda, Tarsa, Consultant for: Merck, Amgen, Takeda, Tarsa, Speakers Bureau: Amgen, Pfizer.